The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/su11174747
|View full text |Cite
|
Sign up to set email alerts
|

Is the Environmental Kuznets Curve Still Valid: A Perspective of Wicked Problems

Abstract: Historically, academia has paid much attention to environmental Kuznets curve (EKC) associated hypotheses, and the EKC per se has triggered conflicting reactions since first posited. Yet, all controversies seem not to have any base framework to address further pollution-related strategies. Built upon an extensive critical review of the extant EKC literature, this paper attempts to address the gap by introducing the theory of wicked problems that can be used to reframe the extant EKC research. Integrating and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…While some studies validate the EKC, others reject this concept. For instance, while Sarkodie and Strezov [22] in their study of three prominent developed economies reported findings that validate the EKC hypothesis using a linear model, Chen et al [23] in their study considered the model inadequate due to the bound rationality of humans. Yet, in all cases, the fact that economic development impacts carbon emissions has never been denied.…”
Section: Literature Reviewmentioning
confidence: 98%
“…While some studies validate the EKC, others reject this concept. For instance, while Sarkodie and Strezov [22] in their study of three prominent developed economies reported findings that validate the EKC hypothesis using a linear model, Chen et al [23] in their study considered the model inadequate due to the bound rationality of humans. Yet, in all cases, the fact that economic development impacts carbon emissions has never been denied.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Consequently, developed countries become specialized in clean and service intensive production without changing their consumption patterns, whereas poor countries are concentrated on dirty and material-intensive production (Cole et al, 2000). This argument raises multifaceted questions about scale, composition and technique effects and income elasticity of environmental quality demand of EKC (Chen et al, 2019). Thus, the progress of technological structure would be offset when final consumption grasps pollution haven (Wagner, 2010).…”
Section: Displacement and Pollution Haven Hypothesismentioning
confidence: 99%
“…Being aware of the importance of involving others in the game is the starting point for this attitude. The more systemic the sustainability challenges are, the more individuals and organizations are required to pool efforts to establish the sustainable solutions [21].…”
Section: Sources Of Motivation and Attitude Formingmentioning
confidence: 99%